Spain : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Supervision, Securities Supervision, Payment Systems, Securities Settlement Systems, and Financial Policy Transparency. (IMF Staff Country Reports; Country Report, 2006)
The Financial System Stability Assessment found the financial sector to be vibrant, resilient, highly competitive, and well supervised and regulated. Stress tests showed credit institutions and insurers to be highly resilient to a variety of shocks. It also found a high degree of observance of the principles dealing with effective supervision by the three regulatory authorities-the Bank of Spain, National Securities Market Commission, and the Directorate General of Insurance and Pension Funds. The Committee on Payment and Settlement Systems Core Principles assessed that all principles are observed by the Real-Time Gross Settlement System.